Assessing and developing the written reflective practice skills of speech-language pathology students. (2nd January 2019) - Cook, Kate; Tillard, Gina; Wyles, Christine; Gerhard, Daniel; Ormond, Tika; McAuliffe, Megan
Abstract: Purpose : Written reflective practice aims to support critical thinking and problem solving skills in speech-language pathology (SLP) clinical education programmes. Yet, there has been limited investigation of students' development of written reflective practice skills over time and during a real-time clinical experience. The purpose of this study was to investigate students' development of breadth and depth of written reflective practice across a six-week clinical experience. Method : Participants were 59 undergraduate and 14 postgraduate SLP students. Participants wrote critical reflections describing an interaction with a client/s at the conclusion of weeks two, four and six of their clinical experience. Formative feedback was provided after each submission. Breadth and depth of reflection were coded using a modification of Plack et al.'s coding schema. Result : There was a statistically significant association between time and likelihood of development of breadth of reflection for the elements process and content. Depth of reflection improved significantly across time. The majority of participants were classified as "reflectors" or critical reflector at the conclusion of the study. Conclusion : SLP students can make significant improvements in both breadth and depth of written reflective practice over a six-week period. Implications for clinical teaching are discussed.